The transformative role of interaction rituals within therapeutic communities - Clarke, Jenelle M.; Waring, Justin (Wiley, 2018)
Mental health settings are fraught with emotion as clients address difficult life experiences and relational patterns. Clients spend a substantial amount of time together outside of structured therapy, but little is known about how these moments are potentially therapeutic, especially as sites of emotional change. We draw on interaction ritual chain theory to explore how negative emotions in situations outside of formal therapy can be transformed into positive emotions and facilitate personal change. The research is based upon a narrative ethnography of two therapeutic communities for individuals with a diagnosis of personality disorder. Despite the presence of negative transient emotions in these rituals, clients experienced positive feelings of solidarity and belonging, and the majority of clients reported increased feelings of confidence and positive change. Conversely, dynamics between clients showed clients were not always supportive of one another and at times, could exclude others, resulting in isolation and alienation. We argue interactions that generate feelings of inclusion or exclusion over time area key component in whether clients gain positive or negative emotional feeling and experience personal change.